2020
DOI: 10.1177/1756284820971202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fungal and bacterial dysbiosis in young adult Chinese patients with Crohn’s disease

Abstract: Intestinal microbiota dysbiosis has been described in inflammatory bowel disease (IBD), but data from China are limited. In this study, we performed molecular analysis of the fecal microbial community from 20 healthy Chinese subjects and 25 patients with Crohn’s disease (CD), and evaluated associations with bacterial and fungal compositions. Decreased richness and diversity of bacterial composition was observed in the CD group compared with healthy (H) subjects. Significant structural differences in bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 46 publications
(93 reference statements)
4
44
1
Order By: Relevance
“…We show here that the diversity of the intestinal microbiota decreased in patients with UC or pouchitis as previously reported and that UC and pouchitis were associated with different microbial structures compared with the control group [26]. When it comes to active UC, though evidence indicates that Lachnoclostridium contributes to produce sul de that inhibits butyrate utilization [27], and Peptostreptococcuse triggers a pro-in ammatory response based on activating nuclear factor kappa-B(NF-κB) activation, the increased abundance of these bacteria suggests that their role in promoting the occurrence of UC is limited(Fig. 1b) [28].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We show here that the diversity of the intestinal microbiota decreased in patients with UC or pouchitis as previously reported and that UC and pouchitis were associated with different microbial structures compared with the control group [26]. When it comes to active UC, though evidence indicates that Lachnoclostridium contributes to produce sul de that inhibits butyrate utilization [27], and Peptostreptococcuse triggers a pro-in ammatory response based on activating nuclear factor kappa-B(NF-κB) activation, the increased abundance of these bacteria suggests that their role in promoting the occurrence of UC is limited(Fig. 1b) [28].…”
Section: Discussionsupporting
confidence: 81%
“…Some patients present Crohn's-like (CD) disease of the pouch. Interestingly, the bloom of E. coli, Ruminococcus_gnavus, and the consumption of Faecalibacterium are prominent microbiological features of CD [39][40]. Pouchitis and CD share certain similarities such as predisposition to perianal infection and anal stula, which may be associated with speci c pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The above results were in line with a gradual decrease in the levels of SCFA-producing microbiota in the progression of AD ( Zhuang et al., 2018 ). Among these decreased butyrate-producing microbiota genera in the SCD group compared to the NC group, Fusicatenibacter in family Lachnospiraceae , which increases butyrate production in stool samples ( Weis et al., 2019 ), maintains the integrity of the gut barrier and downgrades inflammation ( Koh et al., 2016 ; Zheng et al., 2017 ), was also decreased in patients with cirrhosis, PD, ulcerative colitis, and Crohn’s disease ( Takeshita et al., 2016 ; Jin et al., 2019 ; Weis et al., 2019 ; Qiu et al., 2020 ). The low abundance of Ruminococcaceae_UCG-005 within the family Ruminococcaceae in SCD patients was in keeping with the findings of a report on patients with depression ( Jiang et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fungi are suggested to influence intestinal health and disease by suppressing the outgrowth of potential pathobionts, promoting immunoregulatory pathways, and modulating host metabolism ( Huseyin et al, 2017 ; Ni et al, 2017 ; Sam et al, 2017 ; Chin et al, 2020 ). Several clinical studies have identified a distinct fungal microbiota dysbiosis in inflammatory bowel disease (IBD), primary sclerosing cholangitis, asthma, type 2 diabetes mellitus, chronic liver diseases, Parkinson’s disease and other neurological diseases, and even colorectal cancer ( Hoarau et al, 2016 ; Sokol et al, 2017 ; Forbes et al, 2018 ; Coker et al, 2019 ; Cirstea et al, 2020 ; Jayasudha et al, 2020 ; Jiang et al, 2020 ; Lemoinne et al, 2020 ; Qiu et al, 2020 ; van Tilburg Bernardes et al, 2020 ; Ventin-Holmberg et al, 2020 ). Studies of animal models have found that commensal fungi can activate host-protective immune pathways related to epithelial barrier integrity, but can also induce reactions that contribute to events associated with IBD ( Iliev and Cadwell, 2020 ).…”
Section: Introductionmentioning
confidence: 99%